Rapid detection of functional gene polymorphisms of TLRs and IL-17 using high resolution melting analysis - Teräsjärvi J; Hakanen A; Korppi M; Nuolivirta K; Gröndahl-Yli-Hannuksela K; Mertsola J; Peltola V; He QS (NATURE PUBLISHING GROUP, 2022)
Genetic variations in toll-like receptors (TLRs) and IL-17A have been widely connected to different diseases. Associations between susceptibility and resistance to different infections and single nucleotide polymorphisms (SNPs) in TLR1 to TLR4 and IL17A have been found. In this study, we aimed to develop a rapid and high throughput method to detect functional SNPs of above mentioned proteins. The following most studied and clinically important SNPs: TLR1 (rs5743618), TLR2 (rs5743708), TLR3 (rs3775291), TLR4 (rs4986790) and IL17 (rs2275913) were tested. High resolution melting analysis (HRMA) based on real-time PCR combined with melting analysis of a saturating double stranded-DNA binding dye was developed and used. The obtained results were compared to the "standard" sequencing method. A total of 113 DNA samples with known genotypes were included. The HRMA method correctly identified all genotypes of these five SNPs. Co-efficient values of variation of intra-and inter-run precision repeatability ranged from 0.04 to 0.23%. The determined limit of qualification for testing samples was from 0.5 to 8.0 ng/mu l. The identical genotyping result was obtained from the same sample with these concentrations. Compared to "standard" sequencing methods HRMA is cost-effective, rapid and simple. All the five SNPs can be analyzed separately or in combination.